2013
DOI: 10.1186/1687-9856-2013-10
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the parental origin of the X-chromosome on the clinical features, associated complications, the two-year-response to growth hormone (rhGH) and the biochemical profile in patients with turner syndrome

Abstract: BackgroundIt is possible that genes on the X chromosome are expressed differently depending of its parental origin. The objective of this study was to determine the influence of the parental origin of the X-chromosome on phenotypic variability, response to rhGH and on the biochemical profile of TS patients.MethodsThis was a cross-sectional multicenter correlational study carried out over three years in six Latin-American university hospitals. Unrelated 45,X TS patients (n =  93; 18.3 ± 8.5 years )) were evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 28 publications
3
16
0
Order By: Relevance
“…However, patients with monosomy X tend to have the most severe phenotype. The results of studies assessing the impact of X origin (maternal/paternal) on TS phenotype are inconclusive (4,6,7,8). The isoX anomaly is often associated with autoimmunity, whilst the ring X karyotype is also associated with psychological and learning difficulties (9,10,11).…”
Section: Introductionmentioning
confidence: 99%
“…However, patients with monosomy X tend to have the most severe phenotype. The results of studies assessing the impact of X origin (maternal/paternal) on TS phenotype are inconclusive (4,6,7,8). The isoX anomaly is often associated with autoimmunity, whilst the ring X karyotype is also associated with psychological and learning difficulties (9,10,11).…”
Section: Introductionmentioning
confidence: 99%
“…Most of these studies were small series including 4-39 live-born patients with Turner syndrome [20,23,24,[32][33][34][35][36]. The 2 largest series with 97 children [5] and 93 prepubertal patients [37] showed rates in the lower range (71-72%).…”
Section: Discussionmentioning
confidence: 99%
“…A proportion of her cells contained two X chromosomes (28%), whereas the rest had only one X chromosome (72%). Most of the studies which have targeted the parental origin of the X chromosome in Turner syndrome have shown that, in the majority of monosomy Turner syndrome patients, the paternal X chromosome was lost and approximately 70% of patients retained a maternal X chromosome (Alvarez‐Nava et al, ). High myopia is documented to be the most striking phenotypic feature in affected females, which could be the earliest and most reliable guide to the affected female with XLRP (Al‐Maskari, O'grady, Pal, & McKibbin, ).…”
Section: Dicussionmentioning
confidence: 99%